Moderate alcohol consumption aggravates high-fat diet induced steatohepatitis in rats - Wang, Yan; Seitz, Helmut K.; Wang, Xiang-Dong (Alcoholism, 2010)
Background: Nonalcoholic steatohepatitis (NASH) develops in the absence of chronic and excessive alcohol consumption. However, it remains unknown whether moderate alcohol consumption aggravates liver inflammation in pre-existing NASH condition.